Application of the superconducting fault current limiter strategy to improve the fault ride-through capability of a doubly-fed induction generator–based wind energy conversion system. (December 2015) - Sitharthan, R; Geethanjali, M
The enormous demand for electricity is partially satisfied by the increased penetration of wind power generation resources. This necessitates a wind energy conversion system (WECS) to remain connected to the grid in order to maintain power system stability during grid faults. This paper proposes a superconducting fault current limiter control strategy to improve the fault ride-through (FRT) capability of a doubly-fed induction generator (DFIG)-based WECS during grid faults. The outstanding aspect of the proposed technique is that it reduces the fault current level at the stator side and suppresses the rotor inrush current during incidents of grid faults. Consequently, the oscillation in the DC-link voltage and the electromagnetic torque of the WECS are reduced to a minimum permissible limit. Therefore, the proposed strategy improves the FRT capability of the WECS. Thus, the WECS remains connected to the grid and contributes necessary power system stability during and after the grid faults. The effectiveness of the proposed strategy is studied through a time domain simulation carried out in a MATLAB/Simulink environment.